PENGARUH PENGGUNAAN MEDIA BERBASIS PADLET DALAM PELAJARAN IPA SISWA KELAS V SDN SIPALA 1 MAKASSAR - Muh Saiful Perdana S; Maman A Majid Binfas, Maman A Majid Binfas; Andi Adam, Andi Adam; Wahyuddin, Wahyuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Padlet media is a digital learning tool that teachers and students can easily use for distance learning. Research on the Use of Padlet-Based Media in Science Lessons for Grade V Students at SDN Sipala 1 Makassar, this study aims to determine the effect of using Padlet-Based Learning Media on student learning outcomes with material let's get acquainted with our earth. This research method is quantitative experiment (true experimental) using pretest-posttest control group design. The results showed a fixed effect of Padlet-Based Learning Media on Science Learning Outcomes as from the results This is shown through descriptive statistical analysis. This can be seen in the average value of the control class posstest of 76.40, while the average value of the experimental class posstest is 78.00. The results of the infrential analysis obtained t-table = 1.667 with the results of the calculation of t-count> t-table 2.310> 1.667. Thus H0 is rejected and acceptance of H1 occurs. So, the result is that there is a significant effect on the use of Padlet-based learning media on the science learning outcomes of fifth grade students at SD Negeri Sipala 1 Makassar.